Comment: Direct Investment, Research Intensity, and Profitability - Upson, Roger B. (Journal of Financial and Quantitative Analysis, 1974)
Dr. Severn and Professor Laurence present an analysis of the relationships between direct investment, research and development (R & D), and profitability. Early in the paper it is stated that the goal is to provide an explanation for the assumed high internal rate of return on investment abroad. Later it is restated that the paper studies “the profitability of the firm as a whole, rather than its reported profit on foreign assets alone.” Consequently, no evidence is presented of a high return on investment abroad. Indeed, the references to rates of return in the first few pages should be preceded by the word “expected” because these are ex ante returns, whereas the returns analyzed elsewhere in the paper are ex post returns.